U.S. exchange upgrades: Reducing uncertainty through a two-stage IPO - Cole, Rebel A.; Floros, Ioannis V.; Ivanov, Vladimir I. (Journal of Financial Intermediation, 2019)
We examine the effects on IPO uncertainty of an alternative going-public mechanism – the two-stage IPO, where a firm first gets quoted on the OTC market, and then upgrades to a national exchange where it first issues public equity. We find that a two-stage IPO firm experiences lower underpricing and return volatility than does a similar traditional IPO firm. Our study is the first to analyze the impact of U.S. pre-IPO disclosure and liquidity on levels of uncertainty and pricing at the IPO stage. We find that greater disclosure and liquidity during the first stage leads to greater reduction in IPO uncertainty. We control for the potentially endogenous nature of the two-stage IPOs by using a difference-in-difference analysis that utilizes two exogenous OTC market events.